Do 16 i starshe . Do 16 i starshe . Under 16 and Over . До 16 и старше - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion on drug addiction; opinions of different youth groups. Featured in the program: Malinin, Aleksandr Nikolaevich (Singer) Series description: TV program of the First channel of Russia and the USSR, dedicated to the problems of young people. The program dealt with the current problems of youth life: homelessness, the movement of "rockers," drug addiction, the problem of "bullying," leisure, and family relations. Обсуждение проблемы наркомании; выступление молодежных групп. В программе участвуют: Малинин, Александр Николаевич (Певец) Описание серии: Телевизионная программа Первого канала СССР и России, посвящённая молодёжи. Программа освещала актуальные проблемы молодежной жизни: беспризорность, движение "рокеров," темы наркомании и "дедовщины," проблемы досуга и взаимоотношений в семье.